A comparative study of high dose vs low dose oxytocin in the augmentation of labour - Rudra, Samar; Rama, Amulya; Subramanian, Supraja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Augmentation of labour is a practice that aims to increase the duration, frequency, and intensity of uterine contractions in order to decrease the duration of labour and reduce adverse events of maternal and fetal outcomes associated with prolonged labour. Although oxytocin is the most commonly used drug for the augmentation of labour, there is no universally accepted dosage regimen as various studies have used different regimens of oxytocin as low dose and high dose, leading to clinical heterogeneity. Hence this study was taken up to study the advantages, disadvantages and complications of a widely accepted regime for this study. Methods: 100 patients in active labour, with inadequate uterine contractions were selected. The patients were randomly selected, allotting alternate cases for high dose and low dose oxytocin. The patients were monitored through the course of labour and compared in terms of augmentation-delivery interval, mode of delivery, maternal and fetal outcome. The findings were tabulated and statistically analyzed. Results: Majority of the patients delivered vaginally in both groups (78% of high dose and 90% of low dose group). The mean augmentation-delivery interval was 7.20 and 7.45 hours for high dose and low dose group respectively. 12% patients in high dose group experienced maternal complications, while none were encountered in low doe group. 12% neonates from high dose group and 14% from low dose group required admission to the NICU. Conclusions: It was concluded with moderate certainty that high dose regimen of oxytocin resulted in reduction in the duration of labour, but cesarean rate, maternal and fetal complications were more. It was concluded that neither regimen has got an absolute advantage or disadvantage over the other.